Seasonality of host immunity in a tropical disease system. Issue 7 (19th July 2022) - Rosa, Gonçalo M.; Perez, Rachel; Richards, Lora A.; Richards‐Zawacki, Corinne L.; Smilanich, Angela M.; Reinert, Laura K.; Rollins‐Smith, Louise A.; Wetzel, Daniel P.; Voyles, Jamie
Abstract: Infectious disease systems frequently exhibit strong seasonal patterns, yet the mechanisms that underpin intra‐annual cycles are unclear, particularly in tropical regions. We hypothesized that host immune function fluctuates seasonally, contributing to oscillations in infection patterns in a tropical disease system. To test this hypothesis, we investigated a key host defense of amphibians against a lethal fungal pathogen, Batrachochytrium dendrobatidis ( Bd ). We integrated two field experiments in which we perturbed amphibian skin secretions, a critical host immune mechanism, in Panamanian rocket frogs ( Colostethus panamansis ). We found that this immunosuppressive technique of reducing skin secretions in wild frog populations increased Bd prevalence and infection intensity, indicating that this immune defense contributes to resistance to Bd in wild frog populations. We also found that the chemical composition and anti‐ Bd effectiveness of frog skin secretions varied across seasons, with greater pathogen inhibition during the dry season relative to the wet season. These results suggest that the effectiveness of this host defense mechanism shifts across seasons, likely contributing to seasonal infection patterns in a lethal disease system. More broadly, our findings indicate that host immune defenses can fluctuate across seasons, even in tropical regions where temperatures are relatively stable, which advances our understanding of intra‐annual cycles of infectious disease dynamics.